Isolasi dan Identifikasi Senyawa Bioaktif Ekstrak Aseton Daun Garcinia lateriflora Blume - SRI HARTATI; DEDE RAHMAWATI; SUJASWADI WIRYOWIDAGDO (Fakultas Farmasi Universitas Pancasila, 2011)
Preliminary studies have been carried out phytochemical test acetone leaf extract Garcinialateriflora Blume., and toxicity test against shrimp larvae (Artemia salina Leach) and murine cell lineP388. Isolates which showed the highest mortality are proceeded further for fractionation, isolation andpurification. The structure identification of active campound carriedout by analyzing the spectrum of IR ,GC-MS (Gas chromatography mass spectrometer) and proton nuclear magnetic resonance spectrometer(1H-NMR ) and (13C-NMR ). The results showed that the most active against the larval shrimp Artemiasalina L. with LC50 value of 18.03 ug/mL is b-asaron, IC50 of test results on cell line murine P-388 is 47.0ug/mL. This compound was isolated first time from the plant Garcinia lateriflora BL.